A dual process perspective on advances in cognitive science and alcohol use disorder. (April 2019) - Lindgren, Kristen P.; Hendershot, Christian S.; Ramirez, Jason J.; Bernat, Edward; Rangel-Gomez, Mauricio; Peterson, Kirsten P.; Murphy, James G.
Abstract: There is a tremendous global and national (US) burden associated with alcohol misuse and alcohol use disorder (AUD). Further, of the mental health disorders, AUD has the widest treatment gap. Thus, there is a critical need for improved understanding of the etiology, maintenance, and treatment of AUD. The application of cognitive science to the study of AUD has a longstanding history of attempting to meet this need. In this selective review, we identified and focused on four domains of recent (i.e., in the last decade) applications of cognitive science to the study of AUD: implicit cognitive biases, executive function, behavioral economic approaches to alcohol decision making, and functional connectivity neuroimaging. We highlighted advances within these four domains and considered them in the context of dual process models of addiction, which focus on the contribution and interplay of two complementary neurocognitive systems (impulsive and control systems). Findings across the domains were generally consistent with dual process models. They also suggest the need for further model refinements, including integrating behavioral economic approaches and findings from functional connectivity neuroimaging studies. Research evaluating candidate interventions associated with these domains is emergent but promising, suggesting important directions for future research. Highlights: We review recent cognitive science advances related to alcohol use disorders. We focus on four domains, including implicit cognitive bias and executive function. Behavioral economic approaches and functional connectivity are also reviewed. We discuss these domains in the context of dual process models. We discuss implications for theory and clinical practice.